Microglial Activation with Reduction in Autophagy Limits White Matter Lesions and Improves Cognitive Defects During Cerebral Hypoperfusion - Yang, Zhao; Zhang, Nan; Shen, Hanchao; Lin, Chuangan; Lin, Li; Yuan, Bangqing (Current Neurovascular Research, 2014)
Microglial activation plays a vital role in the pathogenesis of white matter lesions (WMLs) during chronic cerebral hypo perfusion. Autophagy has been associated with both microglia survival and cell death. Yet, the role of autophagy during microglial activation in chronic cerebral ischemia is still unknown. We used a chronic cerebral hypoperfusion model by permanent stenosis of bilateral common carotid artery in mice to study microglial activation and autophagy. However, the autophagy inhibitor (3-methyladenine) could attenuate microglial autophagic activation, decrease white matter lesions, and improve working memory during chronic cerebral hypoperfusion in mice. In conclusion, chronic cerebral hypoperfusion that leads to microglial activation and autophagy induction exacerbates white matter lesions and cognitive deficits in mice. Our findings represent a potential novel target for chronic cerebral hypoperfusion therapy.
Keywords: cognitive deficits